SEBLAK SEBAGAI IDENTITAS NASIONAL KOTA BANDUNG - Ahnaf, Syauqi; Alodya Shondra, Kalonica; Izzati Yusuf, Kaylla; Athif Anwar, Muhammad (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2024)
This research examines the role of seblak as a distinctive culinary identity of Bandung City and its contribution to the socio-economic aspects of the community. Using a descriptive qualitative research method with secondary data from various literature sources, this study analyzes the history, development, and significance of seblak in cultural and economic contexts. The research findings reveal that seblak, which originated in the 1900s and gained popularity in the 2000s, serves not only as a traditional dish but also as a symbol of regional identity that strengthens community bonds. Innovation in seblak presentation, from its traditional form to modern variations, reflects this culinary item's adaptability to contemporary developments. Economically, the growth of the seblak business contributes to job creation and increased income for local communities. This research concludes that seblak plays a vital role as a bridge between tradition and modernity, while also serving as an effective means of preserving local culture within the national culinary context.